2012
DOI: 10.1353/csd.2012.0076
|View full text |Cite
|
Sign up to set email alerts
|

University-Based Service Learning: Relating Mentoring Experiences to Issues of Poverty

Abstract: We investigated whether participation in a university-based, service learning mentoring program could affect college students' learning about social inequities and the effects of poverty. The program we examined combined four critical components: (a) Mentor training, (b) mentoring youth on-site in their high-poverty environments, (c) mentors' ongoing reflecting, and (d) class discussion of issues related to poverty and social inequities. By analyzing students' ongoing reflective journals in relation to Kolb's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…In an examination of predictors of perceived cultural competence, Teasley, Archuleta, and Miller (2014) found that white social workers had significantly lower levels of perceived cultural competence than African American participants, while controlling for professional experience and geographic location of practice. In another study, Hughes et al (2012) provided evidence for a social justice lens by examining a university-based mentoring program that provided ongoing training about social justice discussion to mentors. Specifically, ongoing support and discussion of social justice topics (e.g., privilege, systemic inequality) was provided to program participants who were predominantly white, middle-class college students serving as mentors to low-income, Black high school students.…”
Section: Race Equity and Social Justice Trainingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an examination of predictors of perceived cultural competence, Teasley, Archuleta, and Miller (2014) found that white social workers had significantly lower levels of perceived cultural competence than African American participants, while controlling for professional experience and geographic location of practice. In another study, Hughes et al (2012) provided evidence for a social justice lens by examining a university-based mentoring program that provided ongoing training about social justice discussion to mentors. Specifically, ongoing support and discussion of social justice topics (e.g., privilege, systemic inequality) was provided to program participants who were predominantly white, middle-class college students serving as mentors to low-income, Black high school students.…”
Section: Race Equity and Social Justice Trainingsmentioning
confidence: 99%
“…In another study, Hughes et al. () provided evidence for a social justice lens by examining a university‐based mentoring program that provided ongoing training about social justice discussion to mentors. Specifically, ongoing support and discussion of social justice topics (e.g., privilege, systemic inequality) was provided to program participants who were predominantly white, middle‐class college students serving as mentors to low‐income, Black high school students.…”
Section: Introductionmentioning
confidence: 99%
“…Eyler and Giles (1999) found that relevant classroom education was a significant predictor of students' ability to apply what they were learning to real-life problems, and Hughes et al (2012) identified the importance of learning about poverty to students' ability to integrate their classroom and service-based learning. Reflection, one of the most cited best practices in service-learning broadly, is what links this direct education with the service experience (Hughes et al, 2012). As with direct education, Eyler and Giles found a positive relationship between reflection and application.…”
Section: Contexts That Facilitate Integrative Learningmentioning
confidence: 99%
“…While service-learning programs have the potential to positively influence college student development, researchers and educators caution that simply performing service does not necessarily ensure that significant learning or beneficial outcomes will occur (Jacoby, 1996;Kendall, 1990). For example, although contact with individuals from different cultural and socioeconomic backgrounds can result in interpersonal growth, it can also challenge students in novel ways Hughes, Steinhorn, Davis, Beckrest, Boyd, & Cashen, 2012, Kronick & Cunningham, 2013. This may be especially true when college students enter into mentoring relationships with youth.…”
Section: Challenge and Support In Service-learningmentioning
confidence: 99%
“…Results from this study suggest that support from their peers may allow students to grow from the experience and approach cultural difference with empathic understanding. This explanation is informed by the literature on the cultural challenges of service-learning and mentoring and the importance of support in meeting these challenges Hughes, Steinhorn, Davis, Beckrest, Boyd, & Cashen, 2012, Kronick & Cunningham, 2013. As important as it is that servicelearning experiences provide college students with cultural "stretching" opportunities, a high level of perceived support may also be needed to help them advance their ethnocultural empathy.…”
Section: Connecting Findings To Theorymentioning
confidence: 99%